Recovery after shoulder injury in professional tennis players - Teixeira Silva, R. (2002)
The shoulder joint is a common site of injury in professional tennis players. It is therefore important that sports medicine physicians diagnose and treat shoulder injuries correctly, in order to prevent professional and junior athletes from being sidelined for long periods of time. The article gives advice about diagnosis and treatment of shoulder injuries in tennis players as well as about rehabilitation and return to competition.